2023
DOI: 10.1080/2162402x.2023.2284486
|View full text |Cite
|
Sign up to set email alerts
|

Trial watch: beta-blockers in cancer therapy

Killian Carnet Le Provost,
Oliver Kepp,
Guido Kroemer
et al.

Abstract: Compelling evidence supports the hypothesis that stress negatively impacts cancer development and prognosis. Irrespective of its physical, biological or psychological source, stress triggers a physiological response that is mediated by the hypothalamic-pituitary-adrenal axis and the sympathetic adrenal medullary axis. The resulting release of glucocorticoids and catecholamines into the systemic circulation leads to neuroendocrine and metabolic adaptations that can affect immune homeostasis and immunosurveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 193 publications
(185 reference statements)
0
0
0
Order By: Relevance
“…The clinical trial by Cui et al reported that low plasma level of epinephrine was significantly correlated with better recurrence-free and overall survival in breast cancer patients [62]. In line with this, data extracted from retrospective studies in which some patients incidentally received betablockers revealed better outcomes after cancer surgery [64]. A few prospective studies also supported that beta-blockers reduced the incidence of recurrence and the risk of progressive disease [65,66].…”
Section: Psychological Stressmentioning
confidence: 84%
“…The clinical trial by Cui et al reported that low plasma level of epinephrine was significantly correlated with better recurrence-free and overall survival in breast cancer patients [62]. In line with this, data extracted from retrospective studies in which some patients incidentally received betablockers revealed better outcomes after cancer surgery [64]. A few prospective studies also supported that beta-blockers reduced the incidence of recurrence and the risk of progressive disease [65,66].…”
Section: Psychological Stressmentioning
confidence: 84%